ETIOLOGI KRIMINAL KEJAHATAN SEKSUAL DI WILAYAH HUKUM POLRES PURBALINGGA - Wahyu Dian Rahmah Hanny (Jurnal Idea Hukum, 2016)
The phenomenon of child sexual Purbalingga either categorized as criminal offenses in the category of sexual or violate public decency value, must be addressed. Based on the facts presented and the author of an influential hypothesis, of course, needs to be studied scientifically. Therefore, the authors consider it necessary to examine the etiology of criminal sexual crime in the region hokum Kepolisian Resort Purbalingga. This study aimed to identify and analyze the factors that influence the occurrence of sexual criminal offense in the jurisdiction of Police Purbalingga, and also to know and analyze the response of law enforcement authorities against criminal acts of sexual symptoms in the jurisdiction of Police Purbalingga. Based on this writer uses juridical methods sociological answer the problem formulation.The study states that, the factors that influence the occurrence of sexual crimes in the jurisdiction of Police Purbalingga is a factor of personal, social and cultural. In the context of individual factors or personal, encouragement of individuals who are affected by stimulus negatives that go through the learning process of self-offender among others viewed video porn, the needs of sexual desire, drinking, promiscuity negative, as well as social media that support the modus operandi , In the social construction of gender occurs reversibility, besides the cultural factors relating primarily to the culture of sexuality in any jurisdiction in Purbalingga with sexual criminal act, but its influence is very low, just as the foundation of modernity and lifestyle patterns in Kabupatren Purbalingga. The response of law enforcement authorities against criminal acts of sexual symptoms in Purbalingga among others by conducting preventive and repressive measures. Based on these facts then, should be done legal counseling, sex education counseling, legal protection of children, legal sanctions have sex with children by law enforcement officials, namely the police and prosecution. It also should be formed of local government policies towards employment equity between women and men, as well as the judge gave the maximum punishment for perpetrators of sexual criminal acts involving child victims.Â Keyword: etiology criminal, criminal sexs